Crafting and analyzing nonwovens enhanced with antimicrobial metal particles and diverse mechanisms via substitution reaction - Shou, Bing-Bing; Li, Ting-Ting; Hu, Xian-Jin; Liu, Guo-Hua; Ren, Hai-Tao; Lin, Jia-Horng; Xie, Jingwei; Liu, Li-Yan; Lou, Ching-Wen (Materials today chemistry, 2024)
Bacterial infections result in serious impacts on human health. Non-toxic, potent, and flexible antimicrobial particles loaded onto nonwoven materials offer a promising solution. Metallic antimicrobial particles have achieved significant attention and application; however, common materials such as silver and copper exhibit potential toxicity and typically employ a singular antimicrobial mechanism. This limitation can diminish their effectiveness over the service cycle. In our research gallium (Ga), known for its activity and versatile antimicrobial mechanisms, was employed with ferrous ions (Fe2+), which offer broad-spectrum antimicrobial properties and lower potential toxicity compared to silver and copper. Through spontaneous substitution reaction. Ga and Fe2+ can generate Ga–Fe alloys and various antimicrobial particles. In this study, we developed antimicrobial nonwovens by loading them with multiple types of metal antimicrobial particles through a simple soaking and surface treatment process. The multifaceted antimicrobial mechanisms introduced by these multiple particles provide the nonwoven materials with exceptional antimicrobial performance, achieving an effectiveness of up to 99.99 % against Escherichia coli and Staphylococcus aureus. The feasibility of the substitution reaction between Ga and Fe2+ was thoroughly verified through theoretical calculations, X-ray photoelectron spectroscopy (XPS) characterization, and experimental observations. This research offers valuable insights for advancing and exploring antimicrobial nonwoven materials. [Display omitted] •Improvement of adhesion fastness by electrosubstitution and phase separation.•No toxic organic solvents are used in the preparation process.•The nonwovens are loaded with various antimicrobial particles.•The nonwovens have excellent contact and dissolution antimicrobial effects.•High antimicrobial resistance after conventional autoclave sterilization.